Acridine derivatives as inhibitors/poisons of topoisomerase II - Kozurkova, Maria (JAT. Journal of applied toxicology, 2022)
The potential of acridines (amsacrine) as a topoisomerase II inhibitor or poison was first discovered in 1984, and since then, a considerable number of acridine derivatives have been tested as topoisomerase inhibitors/poisons, containing different substituents on the acridine chromophore. This review will discuss a series of studies published over the course of the last decade, which have investigated various novel acridine derivatives against topoisomerase II activity.
Keywords: jedy; Acridines; Poisons; DNA-topoisomerasy typu II; Antineoplastic Agents; protinádorové látky; Amsacrine; akridiny; DNA Topoisomerases, Type II; amsakrin